TINJAUAN TERHADAP PENYELESAIAN SENGKETA INTERNASIONAL PADA PENETAPAN BATAS KAWASAN ANTAR NEGARA (STUDI KASUS SENGKETA WILAYAH AMBALAT ANTARA NEGARA INDONESIA DENGAN NEGARA MALAYSIA) - Melfa Yuliana Andi Padelang; Ida Kurnia (Jurnal Hukum Adigama, 2022)
The decision of the International Court of Justice in the cases of Sipadan and Ligitan Islands is to hand over the sovereignty of these to Malaysia. However, this decision only states the status of the island, not the status of the waters. Such a decision has created a new dispute, namely the dispute over maritime boundaries. The continental shelf boundary dispute occurred in 2005 due to Indonesia and Malaysia granting overlapping concessions to Unocal and Shell to explore the Ambalat Block. The problems formulated are how the provisions in UNCLOS 1982 to resolve maritime territorial disputes Indonesia and Malaysia in the Ambalat Block and the Sulawesi Sea after the decision of the International Court of Justice on the sovereignty of Sipadan Island and Ligitan. This study uses normative legal research whose approach is based on library materials or secondary data. The results showed that; First, the process of resolving territorial disputes (delimitation) in the Exclusive Economic Zone and the Continental Shelf through negotiation (Articles 74 and 83 of UNCLOS 1982). Second, the settlement of boundary disputes between the Exclusive Economic Zone and the Continental Shelf between Indonesia and Malaysia after the decision of the International Court of Justice on the sovereignty of Sipadan and Ligitan Islands needs to be followed up by the two countries, from the results of the study it appears that no agreement has been reached on this matter. However, both countries can submit disputes through mediation and or other dispute resolution facilities known in international law.